Effects of a school-based karate intervention on academic achievement, psychosocial functioning, and physical fitness: A multi-country cluster randomized controlled trial - Tania Pinto-Escalona; Erica Gobbi; Pedro L. Valenzuela; Simon J. Bennett; Pierluigi Aschieri; Manuel Martin-Loeches; Antonio Paoli; Oscar Martinez- (Elsevier, 2024)
Purpose: To examine the effects of a school-based karate intervention on academic achievement, psychosocial functioning, and physical fitness in children aged 7-8 years. Methods: Twenty schools in 5 different European countries (2 second-grade classrooms per school) participated in a cluster randomized controlled trial (Sport at School trial). Participants were assigned to either a control group, which continued with their habitual physical education lessons, or to an intervention group, which replaced these lessons with a 1-year karate intervention (Karate Mind and Movement program). A total of 721 children (344 girls and 377 boys, 7.4 ± 0.5 years old, mean ± SD) completed the study, of which 333 and 388 were assigned to the control group and intervention group, respectively. Outcomes included academic performance (average grade), psychosocial functioning (Strengths and Difficulties Questionnaire for parents), and different markers of physical fitness (cardiorespiratory fitness, balance, and flexibility). Results: The intervention provided small but significant benefits compared to the control group for academic achievement (d = 0.16; p = 0.003), conduct problems (d = -0.28; p = 0.003), cardiorespiratory fitness (d = 0.36; p < 0.001), and balance (d = 0.24; p = 0.015). There was a trend towards significant benefits for flexibility (d = 0.24; p = 0.056). No significant benefits were observed for other variables, including psychosocial difficulties, emotional symptoms, hyperactivity/inattention, peer problems, or prosocial behaviour (all p > 0.05). Conclusion: A 1-year school-based karate intervention was effective in improving academic achievement, conduct problems, and physical fitness in primary school children. The results support the inclusion of karate during physical education lessons.